2020
DOI: 10.1016/j.metop.2020.100056
|View full text |Cite
|
Sign up to set email alerts
|

Level of glycemic control and its associated factors among type II diabetic patients in debre tabor general hospital, northwest Ethiopia

Abstract: Introduction Poor glycemic control is the major risk factor for the development of acute and chronic diabetes complications. There are limited studies on the level of glycemic control and its associated factors among diabetic patients. So, this study aimed to assess the level of glycemic control and its associated factors among type II DM patients in Debre Tabor General Hospital. Methods An institution based cross sectional study was conducted from November 1–30, 2017. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
30
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 38 publications
(44 reference statements)
9
30
2
Order By: Relevance
“…30 On the other hand, this prevalence was lower compared to findings of Tikur Anbessa hospital (80%), 22 Saudi Arabia (74.9%), 24 Bangladesh (82%), 18 and India (78.2%). 17 A thirty-three 33 percent reduction in poor plasma glucose maintenance was observed among those with a diploma compared to those with no education, which is in line with studies in Debre Tabor referral hospital, 19 and Bangladesh. 18 Possible justification for this might be that medication and practice of lifestyle and recommendations require knowledge or intellectual stimulation, which educated people have.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…30 On the other hand, this prevalence was lower compared to findings of Tikur Anbessa hospital (80%), 22 Saudi Arabia (74.9%), 24 Bangladesh (82%), 18 and India (78.2%). 17 A thirty-three 33 percent reduction in poor plasma glucose maintenance was observed among those with a diploma compared to those with no education, which is in line with studies in Debre Tabor referral hospital, 19 and Bangladesh. 18 Possible justification for this might be that medication and practice of lifestyle and recommendations require knowledge or intellectual stimulation, which educated people have.…”
Section: Discussionsupporting
confidence: 84%
“…The prevalence of poor plasma glucose maintenance was 65.1% which is supported by studies in Gondar hospital (60.5%), 28 Nekemte Referral Hospital, 20 Debre Tabor referral hospital (71.4%), 19 Ethiopian tertiary hospitals (68.3%), 15 and Morocco (66.3%). 21 However, this result was higher than in Ambo hospital (50%), 29 and China (49.3%).…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…11 Poor glycemic control is a major public health issue among patients with type 2 diabetes mellitus and a significant risk factor for the progression of diabetic complications. [12][13][14] Poor glycemic control is a common problem in different parts of the world. Observational studies were conducted worldwide and revealed the magnitude of poor glycemic control ranges from 50.1% to 91.8%.…”
Section: Introductionmentioning
confidence: 99%